Endoscopic surveillance of gastric cancers after Helicobacter pylori eradication - Kobayashi, Masaaki (World J Gastroenterol, 2015)
The incidence and mortality of gastric cancer remains high in East Asian countries. Current data suggest that Helicobacter pylori (H. pylori) eradication might be more effective for preventing gastric cancer in young people before they develop atrophic gastritis and intestinal metaplasia. However, the long-term effect of H. pylori eradication on metachronous cancer prevention after endoscopic resection (ER) of early gastric cancer remains controversial, with some discordance between results published for Japanese and Korean studies. The detection ability of synchronous lesions before ER and eradication of H. pylori directly influences these results. After eradication, some gastric cancers are more difficult to diagnose by endoscopy because of morphologic changes that lead to a flat or depressed appearance. Narrow-band imaging with magnifying endoscopy (NBI-ME) is expected to be useful for identifying metachronous cancers. However, some gastric cancers after eradication show a “gastritis-like” appearance under NBI-ME. The gastritis-like appearance correlates with the histological surface differentiation of the cancer tubules and superficial non-neoplastic epithelium atop or interspersed with the cancer. Till date, it remains unclear whether H. pylori eradication could prevent progression of gastric cancer. Until we can establish more useful endoscopic examination methodologies, regular endoscopic surveillance of high-risk groups is expected to be the most beneficial approach for detection.